Caveolin-1 rs1997623 variant and adult metabolic syndrome—Assessing the association in three ethnic cohorts of Arabs, South Asians and South East Asians - Al Madhoun, Ashraf; Hebbar, Prashantha; Nizam, Rasheeba; Haddad, Dania; Melhem, Motasem; Abu-Farha, Mohamed; Thanaraj, Thangavel Alphonse; Al-Mulla, Fahd (Frontiers in Genetics, 2022)
Background: Animal and cell model studies have implicated CAV1 in the pathophysiology of metabolic disorders. Our previous studies demonstrated a potential association of CAV1 rs1997623 C/A variant with pediatric metabolic syndrome (MetS) in Arab children. In the present study, we evaluate whether the CAV1 variant associates with MetS Arab adults as well. The association signal is further examined for ancestry-specific variation by considering cohorts of other ethnicities. Method: The CAV1 rs1997623 was genotyped in three cohorts of Arab (n = 479), South Asian (n = 660), and South East Asian (n = 362) ethnic adults from Kuwait. MetS status of the individuals was diagnosed using the IDF criteria (presence of central obesity and at least two abnormalities out of: elevated TG, low HDL, hypertension, or T2D). The quantitative measure of MetS was calculated as siMS = 2 × WC/Height + FBG/5.6 + TG/1.7 + SBP/130–HDL/1.02 for males or HDL/1.28 for females. Allelic associations with quantitative and dichotomous MetS traits were assessed using linear and logistic regression models adjusted for age and sex. In addition, empirical p-values (Pemp) were generated using max(T) permutation procedure based on 10,000 permutations. Results: The CAV1 variant was significantly associated with MetS status (OR = 1.811 [1.25–2.61]; p-value = 0.0015; Pemp = 0.0013) and with siMS (Effect size = 0.206; p-value = 0.0035; Pemp = 0.0028) in the cohort of Arab individuals. The association was weak and insignificant in the South Asian and South East Asian cohorts (OR = 1.19 and 1.11; p-values = 0.25 and 0.67, respectively). Conclusion: The reported association of CAV1 rs1997623 C/A with MetS in Arab pediatric population is now demonstrated in an adult Arab cohort as well. The weak association signal seen in the Asian cohorts lead us to propose a certain extent of ethnic-specificity in CAV1 rs1997623 association with MetS.